CLOSING DIPHTHONGS AMONG JAVANESE LEARNERS OF ENGLISH - Widagsa, Rudha (Journal of Foreign Language Teaching and Learning, 2017)
The current study investigated the experiences and linguistic self-concept of six EFL teachers from Indonesia in a Study Abroad (SA) program. The participants were six EFL teachers who were in their first year of an SA program in the United States of America. All of them were enrolled as students in postgraduate programs in different universities in the U.S. when the data were collected. The data collection was conducted through semi-structured interviews through videocalls. The study found that the participants encountered linguistics experiences related to certain linguistic features and culture. In addition to those experiences, certain forms of linguistic selfconceptwere also found. Participants? linguistic self-concept showed that they perceived that theywere not proficient enough in English, their English was very formal, they were proficient oncertain area, and their struggle was not a unique experience. It can be concluded that as learnersin an SA program, EFL teachers experienced what were normally experienced by learners in an SAprogram in general.